PENGEMBANGAN INDEKS KEPATUHAN KUALITAS AIR UNTUK EVALUASI KINERJA INSTALASI PENGOLAHAN AIR DI KABUPATEN GORONTALO - Aristi Ayuningsi Ode Asri; Dwianto (Composite Journal, 2026)
The performance of Water Treatment Plants (WTPs) is generally evaluated by assessing compliance with individual quality standards, without producing an integrated performance metric. As part of a Compliance-Based Evaluation Framework, this study developed the Water Quality Compliance Index (WQCI / Indeks Kepatuhan Kualitas Air, IKKA) to evaluate the performance of six WTPs in Gorontalo Regency: Pulubala, Tilango, Pilohayanga, Bulota, Tabongo, and Biyonga. Primary data consisting of laboratory test results for 11 physicals (5 parameters), chemical (4 parameters), and microbiological (2 parameters) quality parameters were compared against the standards set out in Minister of Health Regulation No. 2 of 2023. The WQCI for each WTP was calculated as an unweighted ratio of the number of parameters meeting quality standards to the total of 11 parameters evaluated, while aspect-level indices were calculated per parameter category across all six WTPs. Results showed that the chemical aspect achieved full compliance (100%; 24/24 evaluations), the physical aspect reached 83.3% (25/30), and the microbiological aspect was the weakest at 16.7% (2/12). Total coliform exceeded standards at all six WTPs, E. coli exceeded standards at four, and turbidity failed at five of six WTPs. WQCI values ranged from 72.7% to 90.9%, classified into three performance categories: "Satisfactory" (72.7%; Tilango, Pilohayanga, Bulota, Tabongo), "Good" (81.8%; Pulubala), and "Very Good" (90.9%; Biyonga), with a system-wide average WQCI of 77.3% ("Satisfactory"). The critical parameters identified were turbidity and coliform bacterial contamination. Technical recommendations therefore focused on optimizing filtration, strengthening disinfection, and controlling contamination in the distribution network.